Intelligent applications in substations disturbance analysis - Kezunovic, M. (2004 IEEE Power Engineering Society General Meeting, 2004)
This paper is prepared for a panel session titled "Intelligent Applications in Substations" and represents a summary of the presentation on the subject of disturbance analysis. The topics covered by this presentation include the use of the following intelligent system techniques: expert systems, neural networks, fuzzy logic, genetic algorithms and advanced signal processing. The applications covered are all related to different aspects of automated analysis of disturbances ranging from classification of faults and power quality disturbances to automated analysis of faults and fault clearing sequences. Each of the mentioned implementations is developed by the author of this paper and his research team, and demonstrated using utility data.